Valorização e identificação de padronagens de ladrilhos hidráulicos de 1920 a 1940, período Art Déco brasileiro, presentes em prédios e casas do centro histórico de Santa Maria/RS - Cortes, Marcele Della Flora (2015)
Architecture is a form of human expression with its surroundings, making the scenery around a living organism in constant evolution and transformation. It is a record of the time that protects artistic, human and cultural expression of people throughout their stories, that is, from past periods buildings that manage to stay in the current landscape, allowing us to know the society, culture, daily life, relationships, materials and technologies used, both for its construction and for arranging the interiors of our ancestors. An example of this was the hydraulic tile, object of study of this research and an important decorative coating, widely used not only in Brazil but worldwide. The hydraulic tile is a form of artistic expression that persists to the present day, where its manual production is increasingly being lost, since currently very few companies still work with the production of these pieces. Thus, this research aims to conduct a survey on the patterning of the samples of hydraulic tile floor coverings that still persevere in real state's Art Déco, consolidated style in the years of 1920-1940, in the boundary of the researched zone: Zone 2, Historical Center of Santa Maria. For a better foundation and greater understanding of the problem, this study used a qualitative and quantitative methodology. It began with a bibliographic research about the main topics to be analyzed during the investigation, such as the history of the city of Santa Maria, its situation during the period under review, the Art Déco, hydraulic coatings used at the time, as well as the hydraulic tile as cultural heritage worthy of preservation. After the search of theoretical basis, began the data collection in the historic center of the city in order to find the remaining hydraulic tiles of the Art Déco period. Thirty-six patterns were found in thirty-two Déco buildings, however, it was realized that the population living in these areas did not have awareness of the importance of preserving these assets accounted for exposing part of our aesthetic architectural, social and cultural heritage. Thus this research also seeks to collaborate with the awareness, knowledge and preservation of the use of hydraulic tile through a brochure that will elucidate the community about the importance of preserving these assets.